Structural Relaxation of Salmon Gelatin Films in the Glassy State - Osorio-Lira, F; Lopez-Angulo, D; Skurtys-Olivier , F; Enrione, J (2012)
Mechanical relaxation of glassy carbohydrates has been reported extensively in the literature; however, little work is available on protein-based systems. This study deals with the structural relaxation of salmon (Salmo salar) gelatin in the glassy state. Skin gelatin was obtained by an acid-alkaline extraction method. Molecular weight (M w) was determined by capillary viscometry. Films prepared by casting (7% w/v) were equilibrated to a moisture content of ~18. 4% (db). The glass transition temperature (T g) and enthalpic relaxation were determined by differential scanning calorimetry (DSC). Mechanical properties were assessed using a texture analyzer at constant temperature and moisture content. DSC showed a T g ~34°C, and the selected storage temperature (T a) was 29°C (T g - T a = 5°C). The films were aged for 0, 4, 8, 16, and 40 h. Viscometry produced values of M w ~90. 2 kDa. The stress relaxation was modeled by the Kohlrausch-Wlliams-Watts (KWW) equation, reporting an increase in relaxation time (? 0) as the ageing time increased (? 0 ~6. 41E + 03 s for 0 h; ? 0 ~9. 01E + 05 s for 40 h). ? parameter was smaller for the aged films, indicating a spread of relaxation times. The derivative of KWW equation (d?/dt) indicated a more rapid relaxation in a fresh sample compared with aged films. DSC showed an excess in enthalpy (?H) on the aged samples due to the non-equilibrium state of the matrix. ?H increased with ageing time with values of ?H ~2. 42 J/g for the films aged for 40 h. This work demonstrated molecular relaxation process of gelatin in the glassy state, which must be taken into account if this material is used as a structure forming matrix. © 2011 Springer Science + Business Media, LLC.